Development and implementation of a miniature RFID system in a shopping mall environment - Ademola Abdulkareem; Awosope C. O. A.; Tope-Ojo A. E. (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The advancement of technology has brought about the need for industrial innovation. One area where innovation is required in a developing country is in the retail industry (this is the focus point of this project) where the present system that is the barcode technology is old and archaic. This project is based on the use of Radio Frequency Identification (RFID) technology to create a faster, easier and more secured checkout system. This paper showcases the development of a miniature RFID desktop application that can be used for registering items coming into a shopping mall, checking out of goods bought from the shopping mall and the detection of an attempt to steal goods from the shopping mall, using both C# programming language and MySQL for the database management.